ENHANCING THAI EFL UNIVERSITY STUDENTS’ READING COMPREHENSION THROUGH A FLIPPED COOPERATIVE CLASSROOM - Chavangklang, Thanaset; Suppasetseree, Suksan (PEOPLE: International Journal of Social Sciences, 2018)
Reading skills are important not only for academic achievement but also for professional development. However, some Thai EFL university students have been found to have relatively low reading comprehension ability, even with those majoring in English. Major causes include lack of reading strategies, improper instructional method, and learning environment. Although providing reading strategies has commonly been used to improve reading comprehension, it is usually effective when providing suitable environments for learning and practicing. Therefore, an alternative instructional method needs to be used in order to provide enhancing learning environments for the maximum learning outcomes. In this study, a Flipped Cooperative Classroom Model (FCCM) is introduced. With this instructional approach, course inputs are learned through online before classroom, and the classroom time is used for more individual practice and group activities. Moreover, both online and classroom learning modes are supported by cooperative activities which help improve reading ability through the group learning process. The objective of this study was to investigate the effectiveness of the FCCM model. The study was implemented with a group of Thai EFL university English-majored students at Nakhon Ratchasima Rajabhat University, through a Reading Comprehension course. The effectiveness of the model was assessed by comparing reading comprehension between the experimental group, learning through the FCCM instructions, and the control group, who learned with conventional classroom. Opinions of students learning with the FCCM method were also investigated. The results showed significant improvement in reading comprehension of the experimental group in comparison to the other group, as well as positive opinions about learning experiences with FCCM.